2022
DOI: 10.9734/sajsse/2022/v14i230374
|View full text |Cite
|
Sign up to set email alerts
|

Smallholder Rice Farmers’ Perceptions on Usefulness of Mobile-Phone Technology in Bahi District, Tanzania

Abstract: Mobile Phone Technology is increasingly becoming a powerful method of interpersonal communication. This paper documents smallholder rice farmers’ perception of the usefulness of this technology in communicating agricultural production and market information. Data were collected from 282 smallholder farmers selected randomly from rice farmers in Bahi District, Tanzania. The findings revealed that 97.2% of the sampled smallholder farmers owned the phone for more than three years. All phones were able to perform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…Studies (Kumar et al, 2022;He et al, 2021;Ireri et al, 2021;Victor et al, 2021;Munyua, 2021) have shown that culture can either support or hinder mobile phone usage awareness and differs across societies in different countries. In Tanzania, studies (Iddi et al, 2023;Kilombele et al, 2023;Kinyashi et al, 2022;Magesa and Mkasanga, 2021;Benard et al, 2020) have mainly focused on accessing business information, farmers' welfare, perceived usefulness and challenges. However, few studies (Summers et al, 2020 andMtega andNgoepe, 2019) on culture and mobile phone revealed that husbands decided on mobile phone ownership and use for married women.…”
Section: Introductionmentioning
confidence: 99%
“…Studies (Kumar et al, 2022;He et al, 2021;Ireri et al, 2021;Victor et al, 2021;Munyua, 2021) have shown that culture can either support or hinder mobile phone usage awareness and differs across societies in different countries. In Tanzania, studies (Iddi et al, 2023;Kilombele et al, 2023;Kinyashi et al, 2022;Magesa and Mkasanga, 2021;Benard et al, 2020) have mainly focused on accessing business information, farmers' welfare, perceived usefulness and challenges. However, few studies (Summers et al, 2020 andMtega andNgoepe, 2019) on culture and mobile phone revealed that husbands decided on mobile phone ownership and use for married women.…”
Section: Introductionmentioning
confidence: 99%
“…Mobile technologies among the people in rural areas play an important role in sustainable rural development as they ensure quick access to information. Studies have shown that mobile technologies through the use of smartphones enable farmers to access information on agriculture, marketing of farm produce and best farming practices (Khan et al, 2020; Kinyashi et al, 2022). Smartphones use different mobile applications that necessitate access to information on health, education and also promote collaboration and communication among people through the use of social media tools (Hamilton et al, 2018; Wohllebe et al, 2021).…”
Section: Introductionmentioning
confidence: 99%